Knowledge And Awareness Of Oral Hygiene Maintenance - A Survey - MATHIVADANI, V.; S, BALAJI GANESH; ARIVARASU, LAKSHMINARAYANAN (The journal of contemporary issues in business and government, 2021)
Oral hygiene maintenance is the important factor for maintaining good oral health and preventing oral disease, Poor oral hygiene can lead to dental caries, periodontal disease, and tooth loss. Etiological factors leading to these oral diseases are genetic predispositions, developmental problems, poor oral hygiene and traumatic incidents. The aim of the study was to evaluate the knowledge and awareness about oral hygiene maintenance among the chennai population. A 20 questionnaires were distributed through online protocols to 200 respondents of the chennai population.20 questions have been distributed which are divided as certain categories which are demographic behaviour, knowledge and perceived benefits. Among a sample of 200 participants 92.08% were aware that improper oral hygiene affects general health and 7.92% were not aware of it , data was collected from filled questionnaires and analysed using SPSS software. Chi square test has been conducted to check the association between the variables involved in this study. Results of this survey concluded that the majority of the population were aware about oral hygiene Maintenance.